'Then May the Deuyls of Hell Be Sayntes Also': The Mediaeval Church in Sixteenth-Century England. Issue 1 (3rd July 2014) - Parish, Helen L.
Abstract : Polemicists on both sides of the religious divide in the sixteenth century turned to the events of the past to legitimate their actions and beliefs. This article examines the way in which the history of the mediaeval Church, but particularly the lives of its saints, was rewritten by English evangelical polemicists in the sixteenth century to meet the needs of the nascent national church. Traditional images of holiness were shattered and definitions of vice and virtue inverted to condemn the saints as the agents of Satan and to reinterpret events in the past which provided unhelpful precedents for the reform of the Church in the sixteenth century.